Composition and organization of highly speciose Empidoidea (Diptera) communities in tropical montane forests of northern Thailand - Plant, Adrian R.; Bickel, Daniel J.; Chatelain, Paul; Daugeron, Christophe; Srisuka, Wichai (Zootaxa, 2019)
This study is based on more than 25,000 specimens of the superfamily Empidoidea (Diptera) collected throughout a full year on a 2000 m elevational habitat succession gradient along a 21 km transect on Doi Inthanon, the highest mountain in Thailand. The samples were sorted to 58 genera and 458 morphospecies (Empididae, 73; Hybotidae, 203; Dolichopodidae, 179; Brachystomatidae, 3).                                                                                                                          The data were used to prepare the first thorough taxon-focussed description of how diversity of a major group of Diptera is structured in tropical forest biotopes. We found significant spatial (elevation / habitat) and temporal (seasonal) variations in richness (α-diversity) and abundance at family-level. α-Diversity of the four families was maximal in damp evergreen forests at higher elevation (1500–2500 m), but Dolichopodidae also had a major subsidiary peak in lowland dry evergreen forest at 500–1000 m. Genus-, tribe- and subfamily level α-diversity / elevation profiles were varied, indicating that overall family-level richness is a composite of many taxa that contribute low, high or mid-elevation specialisms. We provide a detailed analysis of these specialisms for each of the 58 genera. Adult phenology was correlated with the monsoon and had three characteristic phases: (i) pre-monsoon commencement during the latter part of the hot dry season, (ii) a ‘flush’ of maximal richness during the early-monsoon, and (iii) a secondary richness maximum associated with the late-monsoon. Maximum α-diversity occurred in phases (i) and (ii) but communities in phase (iii) had characteristically low evenness in which a few abundant species were dominant. Cluster analysis and ordination resolved three well-founded communities with different species-abundance distributions, high levels of species-level specialism and habitat-fidelity associated with moist hill evergreen forest (MHE) at >2000 m; mid elevation evergreen forests (EM) at 1000–2000 m and dry lowland forest (DL) at <1000 m. The three forest types with which these communities are associated are widespread and typical of northern Thailand and the diversity characteristics of each habitat are likely scalable to larger geographic areas. The transition from lowland DL through to upper montane MHE communities was generally characterised by increasing abundance, lower evenness (higher dominance), slower temporal turnover of community composition (relaxation of seasonality), longer periods of adult flight activity and rare species contributing less to species richness. Oriental biogeographic influences are strong at lower elevations but Palaearctic influences are increasingly important at higher elevations. The mixing of Oriental and Palaearctic elements in MHE forests is thought to explain the greater phylogenetic complexity at higher elevation (as measured by taxonomic distinctness).